2021
DOI: 10.1590/0102-33062020abb0170
|View full text |Cite
|
Sign up to set email alerts
|

Response of mangrove plant species to a saline gradient: Implications for ecological restoration

Abstract: Mangroves are salt tolerant plants that occur in tropical and sub-tropical sheltered coasts. Saltwater intrusions into terrestrial landscapes often occur due to either anthropogenic reasons or natural calamities such as tsunamis. We investigated the potential of using mangrove species for rehabilitation of high saline environments by revealing the capacities of species to remove salt from sediment. We established the salt retention capacity of common mangrove species in Sri Lanka i.e., Rhizophora apiculata, Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…A. marina and R. mucronata were found to survive in a wide range of soil salinity (de Silva and Amarasighe 2021a) and it influences the natural distribution of mangrove species (Ball 1998, Barik et al 2017, De Silva and Amarasinghe 2021a. Results of the current study corroborate this observation, i.e.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A. marina and R. mucronata were found to survive in a wide range of soil salinity (de Silva and Amarasighe 2021a) and it influences the natural distribution of mangrove species (Ball 1998, Barik et al 2017, De Silva and Amarasinghe 2021a. Results of the current study corroborate this observation, i.e.…”
Section: Discussionsupporting
confidence: 84%
“…Besides, our study revealed that salinity of the substrate influences plant biomass or the standing stock of mangrove vegetation, manifesting the effect of salinity on mangrove plant growth and net primary productivity. Increased soil salinity elevates salt content in mangrove plant tissues that decreases water availability causing a decline in productivity (Lovelock et al 2006;Gilman et al 2008;Osland et al 2014;de Silva and Amarasinghe 2021a). As such, our results suggest that local changes in salinity influence the species composition and hence the spatial distribution of mangroves across the island.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation